A whisker-reinforced double-layer porous ceramic plate and its preparation method and application

By using whisker-reinforced double-layer porous ceramic plates, the problem of the difficulty in treating oil-containing wastewater containing solid particulate matter in the prior art is solved, and efficient oil-water separation and solid particulate matter filtration are achieved, which is suitable for industrial applications.

CN118751085BActive Publication Date: 2025-04-25SHANGHAI BAIWEI TECHNOLOGY CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410758389.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-13
Publication Date
2025-04-25
Estimated Expiration
2044-06-13

AI Technical Summary

Technical Problem

The existing oil-water separation technology is difficult to simultaneously treat oil-containing wastewater containing solid particulate matter, and there are problems such as low treatment efficiency, high cost and unfavorable environmental protection.

Method used

A whisker-reinforced double-layer porous ceramic plate is used, which consists of an intercepting layer and a support layer. The intercepting layer has an extremely thin through-pore structure, and the supporting layer has a cavity structure and mesh whiskers. It is prepared by foaming process and buried carbon sintering method. The outer surface layer and the inner pore surface layer form a hydrophilic film layer.

Benefits of technology

It realizes efficient separation of oil-containing wastewater containing solid particulate matter, removes solid particulate matter and oil, has high separation efficiency and is not easy to block, and is suitable for industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118751085B_ABST
    Figure CN118751085B_ABST
Patent Text Reader

Abstract

The present invention discloses a whisker-reinforced double-layer porous ceramic plate and its preparation method and application. The whisker-reinforced double-layer porous ceramic plate includes an interception layer and a support layer. The interception layer has through holes and a thickness of 45-120 μm. The support layer has a cavity structure. The through holes of the interception layer are connected to the cavity structure. The through holes of the interception layer and the cavity structure have whiskers with a mesh structure. The through porosity of the whisker-reinforced double-layer porous ceramic plate is 54%-80%. The whisker-reinforced double-layer porous ceramic plate of the present invention can effectively filter solid particles and separate oil and water, is not prone to clogging, is suitable for treating oily wastewater containing solid particles, and can restore the treatment performance through backwashing technology. It has the characteristics of high performance and low cost and is suitable for industrial applications.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of oil-water separation ceramic materials, and in particular, to a whisker-reinforced double-layer porous ceramic plate and a preparation method and application thereof. Background Art

[0002] Since oily wastewater pollutes the environment, affects the ecological balance, and has a great impact on the human living environment, the treatment of oily wastewater is of great significance to environmental protection and human sustainable development.

[0003] In the prior art, methods for oil-water separation include gravity separation, oxidation-reduction, electrolysis, chemical flocculation, microbial degradation, and membrane filtration. Among them, the gravity separation method uses the density difference between oil and water to gradually gather and float the oil droplets in the sedimentation tank, which has low treatment efficiency, poor effect, large floor space, and cannot treat oil-in-water or water-in-oil oil emulsions; the oxidation-reduction method requires the consumption of oxidants or reductants, the chemical flocculation method requires the consumption of flocculants, and the electrolysis method requires the consumption of a large amount of energy, and the treatment cost is relatively high; the microbial degradation method requires suitable microbial species and breeding conditions, has a limited scope of application, and is relatively costly and difficult. Some of these methods have low treatment efficiency and poor effect, and some require a large amount of consumables or energy, which is costly and not conducive to environmental protection. Moreover, most oily wastewaters also contain solid particles, and the existing treatment methods often require the addition of additional processes for treating solid particles, further increasing the treatment time and treatment cost.

[0004] The membrane filtration method utilizes the tiny holes on the filter material. Substances with smaller particle sizes in the oily wastewater can pass through the membrane, while substances with larger particle sizes are retained. Selecting a membrane with an appropriate pore size can achieve the purpose of oil-water separation, but the flux is low. Moreover, since the oil is retained and adheres to the surface of the membrane, the membrane is easily clogged and difficult to clean. It often needs to be replaced, and the reuse rate is low, which increases the cost of use. Discarded membranes also require higher disposal costs.

[0005] In many cases, oily wastewater may contain solid particles in addition to oil droplets of various particle sizes. The oil-water separation methods in the prior art usually find it difficult to simultaneously achieve solid particle filtration and oil-water separation. There is an urgent need for a material suitable for treating oily wastewater containing solid particles. Summary of the invention

[0006] One purpose of the present application is to provide a whisker-reinforced double-layer porous ceramic plate and a preparation method thereof, so as to solve the problem that the existing oil-water separation technology is difficult to apply to the treatment of oily wastewater containing solid particles.

[0007] In order to achieve the above-mentioned purpose, the first aspect of the present invention provides a whisker reinforced double-layer porous ceramic plate, which includes an intercepting layer and a supporting layer, the intercepting layer has through holes, the thickness of the intercepting layer is 45-120μm, the supporting layer has a cavity structure, the through holes of the intercepting layer are connected to the cavity structure, the through holes of the intercepting layer and the cavity structure have whiskers with a mesh structure, and the through porosity of the whisker reinforced double-layer porous ceramic plate is greater than 50%.

[0008] Furthermore, the through porosity of the double-layer porous ceramic plate is 54%-80%.

[0009] In some embodiments, the ratio of through holes in the intercepting layer having a pore size larger than the preset filtering pore size to the number of through holes having a pore size larger than 5 μm is less than 20%.

[0010] Furthermore, the whiskers are silicon dioxide whiskers, and the diameter of the whiskers is 50-150 nm.

[0011] In some embodiments, the support layer has a thickness of 8-32 mm.

[0012] In some embodiments, the outer surface layer and the inner pore surface layer of the whisker-reinforced double-layer porous ceramic plate have a hydrophilic film layer.

[0013] Furthermore, the hydrophilic membrane layer is an amphoteric fluorocarbon surfactant.

[0014] In some embodiments, the cavity structure of the support layer is formed using a foaming process.

[0015] In some embodiments, the whisker-reinforced double-layer porous ceramic plate is prepared using quartz powder.

[0016] In a second aspect of the present invention, a method for preparing a whisker-reinforced double-layer porous ceramic plate is provided, comprising the following steps: S1, mixing a main material including a first ceramic powder, a single crystal silicon powder and water with an adhesive and a dispersant to form a first mixed slurry, wherein the silicon dioxide content of the first ceramic powder is ≥70%; S2, adding a foaming agent to the first mixed slurry and stirring and mixing to form a foam slurry; S3, injecting the foam slurry into a mold having at least one surface covered with oil paper, and taking out a ceramic rough embryo after natural drying, wherein the contact surface between the ceramic rough embryo and the oil paper forms an interception layer; S 4. Use the second ceramic powder dry powder to fill the pores of the intercepting layer of the ceramic rough blank to form a ceramic blank; S5. Use the carbon-buried sintering method to bury the ceramic blank in carbon for roasting, and heat it to 1000-1200°C at a heating rate of 4-10°C / min, and keep it warm for more than 1 hour to obtain a whisker-reinforced double-layer porous ceramic plate, wherein the main ingredients are as follows in mass percentage: 23-60% of the first ceramic powder, 10-15% of the single crystal silicon powder, 25-67% of water, and 0.3-2% of the total mass of the adhesive, dispersant and foaming agent.

[0017] Furthermore, after the heat preservation step of step S5, the following steps are also included: S6, the ceramic blank obtained by calcination is immersed in an amphoteric fluorocarbon surfactant solution, taken out and dried to obtain a whisker reinforced double-layer porous ceramic plate, wherein the concentration of the amphoteric fluorocarbon surfactant solution is 5% to 8%.

[0018] In some preferred embodiments, the main materials are as follows in terms of mass percentage: 38-50% of the first ceramic powder, 10-12% of the single crystal silicon powder, and 38-52% of water; the adhesive, dispersant, and foaming agent are 1-2%, 1-2%, and 0.3-1% of the total mass of the main materials, respectively.

[0019] In some embodiments, the mesh size of the first ceramic powder is 200-500 mesh. In some embodiments, the silicon content in the single crystal silicon powder is ≥95%, and the mesh size of the single crystal silicon powder is 200-500 mesh. In some embodiments, the first ceramic powder is any one or more of quartz, diatomaceous earth, and silica, and the second ceramic powder is any one or more of quartz, diatomaceous earth, silica, mullite, kaolin, sepiolite, and dolomite.

[0020] Preferably, the first ceramic powder and the second ceramic powder are both quartz.

[0021] In some embodiments, the adhesive is any one or more of sodium carboxymethyl cellulose, hydroxyethyl cellulose, xanthan gum, and gelatin.

[0022] In some embodiments, the foaming agent is any one or more of sodium dodecyl sulfate, sodium dodecylaminopropionate, triethanolamine lauryl sulfate, and carbonates.

[0023] In some embodiments, the dispersant is any one or more of polyvinyl alcohol, polyvinyl alcohol copolymer, modified starch, silicone polyether emulsion.

[0024] The third aspect of the present invention provides a whisker-reinforced double-layer porous ceramic plate prepared by the above-mentioned preparation method.

[0025] The fourth aspect of the present invention also provides a use of the whisker-reinforced double-layer porous ceramic plate of the present invention in oil-water separation containing solid particles.

[0026] The method for preparing a whisker-reinforced double-layer porous ceramic plate of the present invention adopts a first ceramic powder, a single crystal silicon powder and water as main materials, and based on a foamed ceramic process, uses oil paper on the surface of a mold to make a blank, and further uses dry powder to fill the pores on the surface of the ceramic rough blank, and then buries the prepared ceramic blank in carbon for roasting, and then soaks it in an amphoteric fluorocarbon surfactant solution, so as to prepare a whisker-reinforced double-layer porous ceramic plate comprising an intercepting layer and a supporting layer.

[0027] The whisker-reinforced double-layer porous ceramic plate prepared by the method of the present invention has the following characteristics: it includes an interception layer and a support layer, the interception layer is extremely thin, which is equivalent to the particle size of the ceramic powder particles, and the number of through holes in the interception layer whose pore size is larger than the preset filter pore size is extremely small; the support layer has a cavity structure including a large number of gaps, and the cavity structure has whiskers with a mesh structure.

[0028] When the whisker-reinforced double-layer porous ceramic plate of the present invention is applied to oil-water separation containing solid particles, the interception layer can first intercept a large number of large-diameter oil droplets, and the small-diameter through holes of the interception layer can intercept solid particles with a particle size larger than the through hole diameter. Since the mesh whiskers in the cavity structure of the support layer itself also have hydrophilic and oleophobic properties, the oil-containing emulsion that is not intercepted passes through the through holes of the interception layer and enters the support layer, and is divided into small water droplets and small oil droplets by the whiskers, allowing water to pass smoothly while retaining the small oil droplets in the cavity of the support layer. After a period of use, backwashing technology can be used to remove the solid particles that block the through holes of the interception layer and the oil accumulated in the cavity of the support layer, and restore the filtration flux. Therefore, the whisker-reinforced double-layer porous ceramic plate disclosed in the present invention can effectively treat oil-containing wastewater containing solid particles and remove the solid particles and oil therein.

[0029] In addition, by further selecting quartz ceramic powder as the basic material, the whisker-reinforced double-layer porous ceramic plate prepared has the characteristics of stable physical properties and not prone to expansion, making the present invention suitable for large-scale industrial applications.

[0030] The above is an overview of the present application, which may be simplified, summarized, and have omitted details. Therefore, those skilled in the art should appreciate that this part is only illustrative and is not intended to limit the scope of the present application in any way. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] The above and other features of the present application will be more fully understood through the following description and the attached claims in conjunction with the accompanying drawings. It is understood that these drawings only depict several embodiments of the present application and should not be considered as limiting the scope of the present application. By using the accompanying drawings, the present application will be more clearly and detailed.

[0032] Figure 1 A schematic diagram showing a plurality of first ceramic powder particles 10 forming pores through two-dimensional arrangement;

[0033] Figure 2 A photograph taken when observing the surface of the intercepting layer of a ceramic rough blank prepared in step S3 using a magnifying glass is shown;

[0034] Figure 3 The application step S4 is shown, using the second ceramic powder 20 to Figure 1 Schematic diagram of the ceramic rough interception layer after pore filling;

[0035] Figure 4 A photograph taken when observing the surface of the intercepting layer of a ceramic blank prepared in step S4 using a magnifying glass is shown;

[0036] Figure 5 A SEM photograph of a cross section perpendicular to the intercepting layer of the whisker-reinforced double-layer porous ceramic plate prepared in Example B2 is shown;

[0037] Figure 6 A SEM photograph of a cross section of the support layer parallel to the interception layer of the whisker-reinforced double-layer porous ceramic plate prepared in Example B2 is shown;

[0038] Figure 7 A whisker-reinforced double-layer porous ceramic plate sample prepared using Example B2 is shown;

[0039] Figure 8 Shows the oil and Figure 7 Contact angle of the whisker reinforced double-layer porous ceramic plate sample;

[0040] Fig. 9 Shows Figure 7 Comparison of the medium whisker reinforced double-layer porous ceramic plate sample before and after filtering oily wastewater;

[0041] Fig.10 The filtration flux diagram of using the whisker-reinforced double-layer porous ceramic plate prepared in Example A1 to filter the oily wastewater generated by the cold-rolling galvanizing line of a steel plant is shown;

[0042] Fig.11 A comparison diagram of the whisker-reinforced porous ceramic plate sample prepared in Example D1 before and after filtering oily wastewater is shown;

[0043] Fig.12 A comparison chart of pure water flux tests performed using the whisker-reinforced porous ceramic plates prepared in Example D1 and Example D2 is shown. DETAILED DESCRIPTION

[0044] The technical solution of the present application is described in detail below in conjunction with the accompanying drawings. Without departing from the spirit or scope of the subject matter of the present application, other implementations may be adopted, and modifications, combinations, equivalent substitutions or other changes may be made, all of which clearly constitute part of the content of the present application and are included in the protection scope of the present application.

[0045] The preparation method of the whisker-reinforced double-layer porous ceramic plate of the present application includes steps S1-S5, wherein steps S1 and S2 are used to prepare foam slurry, and the raw materials of the foam slurry include main materials and auxiliary materials, the main materials are as follows in terms of mass percentage: 23-60% of the first ceramic powder, 10-15% of the single crystal silicon powder, and 25-67% of water, and the auxiliary materials include adhesives, dispersants, and foaming agents, all of which are 0.3-2% of the total mass of the main materials; preferably, the first ceramic powder is 38-50%, the single crystal silicon powder is 10-12%, and the water is 38-52%; the adhesive, dispersant, and foaming agent are 1-2%, 1-2%, and 0.3-1% of the total mass of the main materials, respectively. Steps S1-S6 are specifically as follows:

[0046] S1. Mixing the main materials including the first ceramic powder, the single crystal silicon powder and water with the adhesive and the dispersant to form a first mixed slurry.

[0047] The first ceramic powder can be any one or more of quartz, diatomaceous earth, and silica. In some embodiments, quartz powder is preferred; further, in order to reduce costs, waste quartz with a silicon dioxide content of ≥ 70% can be selected. The mesh size of the first ceramic powder can be selected between 200-500 meshes.

[0048] The silicon content of the single crystal silicon powder is ≥95%, and the mesh size of the single crystal silicon powder is 200-500 mesh. The inventors of the present application found that when the single crystal silicon powder is added, in the subsequent step of burying in carbon for calcination, the single crystal silicon can participate in the reaction and induce the growth of silicon dioxide whiskers. Only adding the first ceramic powder with a silicon dioxide content of ≥70% or only adding the single crystal silicon powder cannot form whiskers, and the synergistic effect of the two is required.

[0049] The adhesive is any one or more of sodium carboxymethyl cellulose, hydroxyethyl cellulose, xanthan gum and gelatin, and is used to provide viscosity to the slurry.

[0050] The dispersant may be any one or more of polyvinyl alcohol, polyvinyl alcohol copolymer, modified starch, silicone resin polyether emulsion, etc. The dispersant may evenly disperse the first ceramic powder and the single crystal silicon powder in water. At the same time, the above dispersant also has the function of stabilizing foam. The pre-addition may make the bubbles in the foam slurry of step S2 more durable and stable.

[0051] The stirring and mixing time may be 10 minutes or longer.

[0052] S2. Add a foaming agent into the first mixed slurry and stir to form a foam slurry.

[0053] The foaming agent is any one or more of sodium dodecyl sulfate (K12), sodium dodecylaminopropionate, triethanolamine lauryl sulfate (TD-40), and carbonates. After adding the foaming agent, air can be incorporated into the slurry during the stirring process to form a foam slurry.

[0054] The stirring and mixing time may be 5 minutes or longer, preferably 5 to 10 minutes.

[0055] S3, injecting the foam slurry into at least one mold covered with oil paper, and taking out the ceramic rough embryo after natural drying.

[0056] The shape of the mold can be determined according to the shape of the ceramic rough blank required. The oil paper is a processed paper made by coating tung oil or other drying oil on a flexible surface. The oil paper is covered on the surface of the mold, for example, by pasting the oil paper on at least one surface of the bottom and / or side of the mold, and the surface coated with the drying oil faces outward.

[0057] In the prior art, release paper is usually used on the mold surface to separate the mold and the ceramic rough embryo. Although ordinary release paper can separate the ceramic rough embryo from the mold, it is easy to adhere to the ceramic powder particles.

[0058] In this step, by using oil paper on the surface of the mold, on the one hand, the ceramic slurry can be prevented from sticking to the surface of the mold, and after the slurry is dried, the ceramic rough blank can be easily removed from the mold. On the other hand, the inventors of the present application found that after the foamed slurry is injected into the mold whose surface is covered with oil paper, the ceramic powder particles close to the oil paper are arranged in a two-dimensional manner to form an extremely thin surface layer with a thickness of about 1-2 times the particle size of the ceramic powder. For example, if the first ceramic powder is 200-500 mesh, an interception layer with a thickness of about 45-120μm can be formed. At the same time, since the ceramic powder has an irregular shape, there are pores between the ceramic powder particles close to the oil paper. In addition, due to the presence of bubbles in the foam slurry, the bubbles close to the oil paper cause a large number of pores to appear on the surface, and some pores are even visible to the naked eye. Figure 1 A schematic diagram of pores formed by two-dimensional arrangement of a plurality of first ceramic powder particles 10 is shown. For the sake of convenience, these pores can be divided into small-sized pores 11 and large-sized pores 12. There is no clear dividing line between the pore sizes of the small-sized pores 11 and the large-sized pores 12, and they can be divided according to the needs of filtration. For example, if it is desired to intercept solid particles with a pore size greater than 50 μm, the pores with a pore size less than 50 μm can be called small-sized pores, and the pores with a pore size greater than 50 μm can be called large-sized pores.

[0059] The small-sized pores 11 are suitable for intercepting solid particles larger than the pore diameters of these pores, so the present invention refers to the extremely thin surface layer formed by the ceramic powder near the oil paper as an interception layer, and the pores formed between the ceramic powder particles on the interception layer as through holes passing through the interception layer. The prior art uses ordinary release paper, which is easy to adhere to the ceramic powder particles, and cannot form a two-dimensional arrangement of ceramic powder particles on the contact surface of the ceramic slurry and the release paper.

[0060] The rest of the ceramic rough blank except the interception layer is called the support layer. Unlike the interception layer, the ceramic powder particles in the support layer are connected in a three-dimensional stacking manner. Due to the effect of the foaming agent, a large number of cavity structures are formed inside the support layer. The thickness of the support layer can be controlled by setting the depth of the mold.

[0061] The through holes of the intercepting layer are interconnected with the cavities of the supporting layer to form through holes that penetrate the intercepting layer and the supporting layer.

[0062] In order to fully dry the ceramic rough blank, in some embodiments, the natural drying time is more than 48 hours. In some embodiments, after natural drying, the temperature can be raised to 50° C.-100° C. and continued to dry for more than 3 hours.

[0063] Figure 2 A photograph taken when observing the surface of the intercepting layer of a ceramic rough blank prepared in step S3 using a magnifying glass is shown. From the picture, multiple large-sized pores visible to the naked eye can be seen, and some of the large-sized pores are marked with dotted circles in the picture.

[0064] S4, using a second ceramic powder dry powder to fill the pores of the intercepting layer of the ceramic rough blank to form a ceramic blank.

[0065] The second ceramic powder can be selected from any one or more of quartz, diatomaceous earth, silica, mullite, kaolin, sepiolite, and dolomite; the second ceramic powder can be the same as the first ceramic powder or different from the first ceramic powder. For example, in some embodiments, the first ceramic powder is quartz, and the second ceramic powder is also quartz.

[0066] Step S4 can make the pores of the ceramic rough interception layer whose pore size is larger than the particle size of the second ceramic powder further filled with the second ceramic powder, thereby reducing the proportion of large-pore through-holes. Therefore, the particle size of the second ceramic powder can be selected according to the needs of filtration, that is, according to the size of the preset filter aperture. For example, if it is hoped that the interception layer can intercept solid particles with a particle size greater than 50 μm, a second ceramic powder with a particle size slightly smaller than 50 μm can be used, such as a second ceramic powder that can pass through a 300-mesh sieve but cannot pass through a 350-mesh sieve; if the particle size of the second ceramic powder is much smaller than 50 μm, it may cause overfilling of the pores of the interception layer, seriously reducing its flux. Figure 3The application step S4 is shown, using the second ceramic powder 20 to Figure 1 The schematic diagram of the ceramic rough intercepting layer after pore filling is shown, and the effect of the second ceramic powder filling the large-sized pores 12 is shown in the figure.

[0067] Step S4 can be implemented in the following manner. First, the dry powder of the second ceramic powder is coated on the intercepting layer of the ceramic rough blank, and then the surface of the intercepting layer is cleaned with a brush. The purpose of cleaning is to remove the second ceramic powder particles that fall outside the pores of the intercepting layer, while retaining the second ceramic powder particles that fall into the pores of the intercepting layer. Generally speaking, the more the second ceramic powder dry powder is coated, the more uniform the cleaning is, and the second ceramic powder particles can more fully cover the through holes with pore sizes larger than their particle sizes, thereby reducing the proportion of large-sized through holes that do not meet the filtering requirements. Through proper coating, the proportion of through holes with pore sizes larger than the particle size of the second ceramic powder particles in the intercepting layer can be made lower than a preset value, such as lower than 20%, 10%, 5%, and so on. In the case of sufficient coating, this proportion can even be lower than 1%.

[0068] Figure 4 A photograph taken when observing the surface of the intercepting layer of a ceramic blank prepared in step S4 using a magnifying glass is shown. In the figure, the second ceramic powder is white quartz. It can be seen from the figure that after the pore filling step, most of the large-sized pores are filled with the second ceramic powder particles.

[0069] S5. The ceramic blank is buried in carbon for sintering by a carbon burying sintering method, and the temperature is raised to 1000-1200° C. at a heating rate of 4-10° C. / min, and the temperature is kept for more than 1 hour to obtain a whisker-reinforced double-layer porous ceramic plate.

[0070] The carbon buried sintering method is a method of burying the ceramic blank in carbon and baking the ceramic ingredients in an isolated state. Since a small amount of oxygen remains between the carbon and the ceramic blank, under high temperature, the carbon reacts with oxygen and then reacts with part of the silicon dioxide in the first ceramic powder to produce gaseous silicon monoxide. At the same time, the single crystal silicon powder also reacts with the silicon dioxide, oxygen, etc. in the first ceramic powder to produce gaseous silicon monoxide. Since the gaseous silicon monoxide cannot exist stably below 1500 degrees Celsius, it is decomposed by vapor deposition to generate a mesh structure of silicon dioxide whiskers in the cavity structure of the support layer. Relatively few mesh structure whiskers are also generated on the surface and / or pores of the intercepting layer. The diameter of the whiskers is generally 50-150nm.

[0071] At the same time, the ceramic powder particles are melted and bonded together to form a ceramic material with good mechanical strength, and the mesh whiskers in the cavity of the support layer can further enhance its mechanical strength.

[0072] In order to further enhance the hydrophilic and oleophobic properties of the double-layer porous ceramic plate, after the heat preservation step of step S5, the preparation method of the whisker-reinforced double-layer porous ceramic plate of the present application includes step S6:

[0073] S6. Soaking the ceramic blank obtained by calcination in an amphoteric fluorocarbon surfactant solution, taking it out and drying it, thereby obtaining a whisker-reinforced double-layer porous ceramic plate.

[0074] Among them, the amphoteric fluorocarbon surfactant is a surfactant with a fluorocarbon chain as a non-polar group, which can be used as an anionic surfactant or a cationic surfactant. The amphoteric fluorocarbon surfactant can significantly reduce the surface tension at an extremely low concentration and enhance the hydrophilicity of the surface. In this step, various amphoteric fluorocarbon surfactants that can enhance hydrophilicity can be used, such as Yunqing Chemical RK-8410, DuPont Chemours FS-50, etc., generally using a concentration of 5-8%, and the soaking time can be more than one hour. Soaking the whisker-reinforced ceramic blank in the amphoteric fluorocarbon surfactant solution can form a hydrophilic film layer on the outer surface and the internal pore surface of the whisker-reinforced ceramic blank, significantly reducing its surface tension and enhancing the hydrophilic and oleophobic capabilities.

[0075] The whisker reinforced double-layer porous ceramic plate prepared by the above method has a double-layer structure including an intercepting layer and a supporting layer. The surface of the intercepting layer has through holes with small pore sizes, and the interior of the supporting layer has a cavity structure produced by a foaming process. The through holes of the intercepting layer are interconnected with the cavities of the supporting layer to form through holes that penetrate the intercepting layer and the supporting layer. The through holes and the cavity structure of the intercepting layer contain whiskers with a mesh structure. The outer surface layer and the inner pore surface layer of the whisker reinforced double-layer porous ceramic plate also have a hydrophilic film layer composed of an amphoteric fluorocarbon surfactant. In the present disclosure, the foaming process refers to a process step in which a foaming agent is added to a ceramic slurry during the preparation of a ceramic material to form a cavity structure in the ceramic material.

[0076] It should be noted that in the present disclosure, the mesh number of ceramic powder or single crystal silicon powder refers to the mesh size of the sieve that the ceramic powder or single crystal silicon powder can pass through. In the present disclosure, the corresponding relationship between the mesh size of the sieve and the sieve aperture is shown in the following table:

[0077]

[0078]

[0079] Figure 5 The SEM photograph of the cross section perpendicular to the interception layer of the whisker-reinforced double-layer porous ceramic plate prepared in Example B2 of the second group of examples of the present disclosure below is shown. The interception layer 1 and the support layer 2 are shown as examples, the interception layer 1 has an extremely thin thickness h, and a large number of cavity structures can be seen in the support layer 2.

[0080] Figure 6 A cross-sectional SEM photograph of the support layer of the whisker-reinforced double-layer porous ceramic plate prepared in Example B2, which is parallel to the intercepting layer, is shown. From the figure, it can be seen that after being magnified to a sufficient multiple, the dense network structure whiskers in the cavity structure of the support layer are clearly visible.

[0081] When the whisker-reinforced double-layer porous ceramic plate is used to treat oily wastewater containing solid particles, the wastewater flows through the interception layer, and large oil droplets and solid particles with a particle size larger than the aperture of the interception layer are first blocked by the interception layer. Since the surface of the interception layer is coated with a hydrophilic and oleophobic material, the oil droplets float up after being intercepted, and the solid particles sink after being intercepted. The unintercepted solid particles and the oil-water mixture enter the support layer through the through holes on the surface of the interception layer. Since the thickness of the interception layer is very thin, the small-diameter through holes of the interception layer quickly transition to the large-diameter cavity of the support layer, so that the unintercepted small-diameter solid particles can pass through the support layer smoothly and are not easily blocked. Since there are dense mesh whiskers in the cavity, the oil-water mixture entering the support layer is cut into many small water droplets and small oil droplets by these mesh whiskers, thereby separating the oil and water in the oil-containing emulsion. In addition, due to the hydrophilic membrane layer on the surface of the internal pores, a water film is formed on the surface of the internal pores, which further blocks the small oil droplets and prevents them from adhering to the surface of the pores, while the small oil droplets accumulate in the cavity of the support layer.

[0082] As the use time increases, some through holes of the intercepting layer may be blocked by large-sized solid particles or oil droplets, resulting in a decrease in filtration flux. In addition, the oil droplets accumulated in the support layer need to be removed to reduce mixing into the filtered water. At this time, the structural characteristics of the whisker-enhanced double-layer porous ceramic plate support layer having large-sized cavities and the through holes of the intercepting layer having very small pore sizes can be utilized, and the solid particles or oil droplets attached to the through holes of the intercepting layer can be washed away by backwashing technology, and the oil accumulated in the support layer can be removed at the same time, thereby restoring the filtering capacity of the whisker-enhanced double-layer porous ceramic plate. The specific process of backwashing is as follows: a liquid pump or an air pump is used to apply hydraulic pressure or air pressure from the support layer to the intercepting layer, so that the oil droplets accumulated in the support layer are blown out from the through holes of the intercepting layer in the opposite direction and removed, and at the same time, the solid particles or oil droplets attached to the through holes of the intercepting layer fall off due to the pressure difference. The backwashing time can be comprehensively set according to factors such as the distribution of solid particles in the sewage, the oil content, and the thickness of the support layer. If the distribution of solid particles is not considered, generally speaking, when the thickness of the support layer is fixed, the higher the oil content, the more oil droplets accumulate in the support layer per unit time. In order to remove the oil in time, the backwashing interval is shorter. When the oil content is fixed, the thicker the support layer, the more oil droplets can accumulate in the support layer per unit time, and the longer the backwashing interval. In actual use, it can be started at a certain time interval, or when the flux of oil-water separation drops to a preset value, or when the separation efficiency drops to a preset threshold.

[0083] The whisker-reinforced double-layer porous ceramic plate and the preparation method and application effects of the present application are further described below in conjunction with the embodiments.

[0084] In the present disclosure, the pore size distribution of the through holes of the interception layer is statistically analyzed by cross-sectional direct observation, that is, by taking SEM photos of the interception layer of the whisker-reinforced double-layer porous ceramic plate, the number of through holes of different sizes with a pore size greater than 5 μm per unit area is counted. Since the through holes are irregular in shape, the pore size of the through holes is defined as the average of the diameter of the inscribed circle and the diameter of the circumscribed circle of the through holes.

[0085] In order to clearly illustrate the structure of the whisker-reinforced double-layer porous ceramic plate disclosed in the present invention, it is necessary to further measure the thickness of the interception layer. The thickness of the interception layer can be intuitively understood as the closest distance from the outer surface of the interception layer to the cavity of the support layer. However, due to the randomness of the foaming process, the shape of the bubble structure of the support layer is irregular. Therefore, the distance from different areas of the outer surface of the interception layer to the nearest support layer cavity may be different. Therefore, in the present invention, the thickness of the interception layer of the structure of the whisker-reinforced double-layer porous ceramic plate can be expressed by an interval. The thickness of the interception layer can be obtained by measuring the SEM photograph of the cross-section of the whisker-reinforced double-layer porous ceramic plate perpendicular to the interception layer. The specific measurement process is: select a number of measurement points on the outer surface of the interception layer, and for each selected measurement point, the distance along the direction perpendicular to the outer surface of the interception layer toward the support layer to the aperture of the through hole of the interception layer reaches the preset filtration aperture, which is the thickness of the interception layer in the area where the measurement point is located. A certain statistic of the interception layer thickness measured at multiple measurement points can be used as a measure of the interception layer thickness of the whisker reinforced double-layer porous ceramic plate. For example, the statistic can be the average value, or median value, of the interception layer thickness measured at multiple measurement points, or the average value or median value after removing the maximum and minimum values. Those skilled in the art will appreciate that the locations of the selected measurement points should be as dispersed as possible, and the number of measurement points should be as large as possible to obtain a range of interception layer thickness with higher reliability. In the present disclosure, the average value after removing the maximum and minimum values ​​is used as a measure of the interception layer thickness of the whisker reinforced double-layer porous ceramic plate. In the present disclosure, the preset filter aperture can be set as needed. For example, if it is desired that the interception layer can intercept solid particles with a particle size greater than 50 μm, the preset filter aperture is 50 μm.

[0086] In the present disclosure, the through-porosity refers to the ratio of the total volume of through holes that are interconnected between the inside and outside of a ceramic material to the volume of the ceramic material, which can be measured in the following ways: (1) immersing the ceramic material to be tested in a liquid and measuring the increase in the liquid volume ΔV; (2) calculating its volume Vo based on the external dimensions of the ceramic material to be tested. Then the through-porosity η of the ceramic material to be tested is (Vo-ΔV) / Vo. Those skilled in the art will understand that, in the case where the pore size distribution of the through holes in the intercepting layer is the same, generally speaking, the higher the through-porosity, the larger the volume occupied by the cavity of the supporting layer, and the less likely it is to be blocked. The whisker-reinforced double-layer porous ceramic plate disclosed in the present disclosure is prepared by a foaming process, and its through-porosity is generally greater than 50%, which is specifically related to parameters such as the amount of the foaming agent used and the stirring time, and different through-porosities can be obtained by changing the relevant parameters. The method disclosed in the present disclosure can prepare a whisker-reinforced double-layer porous ceramic plate with a through-porosity of 50%-80%.

[0087] Since the mesh whiskers in the support layer cavity are used to divide the oil-containing emulsion into many small water droplets and small oil droplets, and to prevent the small oil droplets from passing through the support layer. In addition, the support layer is further used to accommodate the separated oil droplets so that the oil droplets can be backwashed out through the through holes of the interception layer by the backwashing technology. Therefore, the support layer needs a certain thickness to prevent the oil droplets from passing through, to accommodate the oil droplets intercepted by the mesh whiskers, and to maintain a certain mechanical strength, so the thickness of the support layer is generally set to be greater than 8mm. Preferably, the thickness of the support layer is set to the range of 8-32mm.

[0088] The present disclosure is further illustrated by examples below. For ease of understanding, the examples of preparing whisker-reinforced double-layer porous ceramic plates using the method of the present disclosure are divided into three groups. Each example uses steps S1-S6, except that the materials and parameters are different. The specific steps of each example are as follows: S1. Stir and mix the main materials including the first ceramic powder, single crystal silicon powder and water with the adhesive and dispersant at a stirring rate of 3000 rpm and a stirring time of 45 minutes to form a first mixed slurry; S2. Add a foaming agent to the first mixed slurry and stir and mix at a stirring rate of 3000 rpm and a stirring time of 10 minutes to form a foam slurry; S3. Inject the foam slurry into a circular mold with oil paper on the bottom, dry it naturally for 60 hours, and heat it to 50°C-1 00℃, and then continue drying for 3 hours, and then take out the ceramic rough blank; S4, use the second ceramic powder to fill the pores of the interception layer of the ceramic rough blank to form a ceramic blank; S5, bury the ceramic blank in carbon twice the thickness of the ceramic blank for baking, and heat it to 1200℃ at a heating rate of 4-10℃ / min, and keep it warm for 3 hours to obtain a whisker-reinforced ceramic blank; S6, place the whisker-reinforced ceramic blank in an amphoteric fluorocarbon surfactant solution and soak it for 1 hour, take it out and dry it, and obtain a whisker-reinforced double-layer porous ceramic plate. Here, the amphoteric fluorocarbon surfactant solution uses 5% DuPont Chemours FS-50 aqueous solution, FS-50 is a kind of amphoteric fluorocarbon surfactant. When immersed in its aqueous solution, it can form a hydrophilic film on the surface of the ceramic blank and the surface of the internal pores.

[0089] In the embodiment of the present disclosure, the preset interception aperture is 50 μm, so the second ceramic powder uses quartz powder with a particle size slightly smaller than 50 μm. Those skilled in the art can select the second ceramic powder with a suitable particle size according to the different preset interception apertures.

[0090] The first group of embodiments includes embodiments A1-A3. In embodiment A1, the main materials are as follows: 38% of the first ceramic powder, 12% of the single crystal silicon powder, and 50% of water in terms of mass percentage, and the auxiliary materials include 1% of the total mass of the main materials as an adhesive, 1% of the dispersant, and 0.7% of the foaming agent. The first ceramic powder is a quartz powder with a silicon dioxide content of 95% and a mesh size of 200 meshes, the single crystal silicon powder has a silicon content of 95% and a mesh size of 200 meshes, the adhesive is sodium cellulose, the dispersant is a polyvinyl alcohol copolymer, and the foaming agent is triethanolamine lauryl sulfate (TD-40).

[0091] The difference between whisker reinforced double-layer porous ceramic plate embodiments A2-A3 and embodiment A1 lies in the mesh size of the first ceramic powder, the mass percentage of single crystal silicon and the mass percentage of water. Other process parameters are the same. The specific parameters and experimental results are shown in Tables 1-1 and 1-2.

[0092] Table 1-1 Parameters of the first group of embodiments

[0093]

[0094] Table 1-2 Experimental results of the first group of embodiments

[0095]

[0096] In this group of embodiments and subsequent embodiments, the proportion of through holes with apertures greater than 50 μm in the interception layer refers to the proportion of through holes with apertures greater than 50 μm in the interception layer to the number of through holes with apertures greater than 5 μm. The interception layer thickness is obtained by taking an SEM photograph of a cross section of the whisker-reinforced double-layer porous ceramic plate perpendicular to the interception layer, selecting 10 measurement points with an interval of 1 mm along the interception layer direction, measuring the interception layer thickness at the measurement points, and removing the maximum and minimum values ​​to obtain the average value of the interception layer thickness at the remaining 8 measurement points.

[0097] In the present disclosure, separation efficiency is defined as the ratio of the difference between the total organic carbon (TOC) of the sewage before filtration and the TOC of the sewage after filtration to the TOC before filtration, expressed as a percentage. Among them, total organic carbon is the total amount of organic matter in the water expressed by the carbon content, expressed as the mass concentration (mg / L) of carbon (C). The higher the TOC value of water, the higher the organic matter content in the water. Therefore, TOC can be used as an indicator for evaluating organic pollution in water quality. The organic matter in oily sewage is mainly oil. Therefore, the separation efficiency defined by the above method can reflect the effect of oil-water separation.

[0098] The oil contact angle refers to the angle between the tangent of the air-oil droplet interface at the intersection of the air, oil droplet and support layer profile and the boundary line of the oil droplet-support layer profile located on one side of the oil droplet. The larger the angle, the worse the wettability of the oil on the solid surface and the stronger the oleophobicity of the experimental product.

[0099] The results of the first group of examples show that as the mesh size of the first ceramic powder and the single crystal silicon powder increases, the through porosity increases, the separation efficiency increases, and the oil contact angle also increases. It can be seen that the larger the mesh size of the first ceramic powder and the single crystal silicon powder, the better the effect, but too high a mesh size will reduce the mechanical strength and affect the service life. As the mass percentage of the single crystal silicon powder increases, the through porosity decreases, the separation efficiency increases, but the oil contact angle decreases instead. When the mesh size of the first ceramic powder is the same, the thickness of the interception layer is not much different.

[0100] The second group of embodiments includes embodiments B1-B3. The main materials of embodiment B1 are as follows: 50% of the first ceramic powder, 12% of the single crystal silicon powder, and 38% of water by mass percentage. The auxiliary materials include 1% of the total mass of the main materials as adhesive, 1% of the dispersant, and 0.7% of the foaming agent. The first ceramic powder is waste quartz powder with a silicon dioxide content of 80% and a mesh size of 325, which is conducive to further reducing costs; the silicon content of the single crystal silicon powder is 95% and the mesh size is 325; the adhesive is xanthocollagen, the dispersant is a polyvinyl alcohol copolymer, and the foaming agent is sodium dodecyl sulfate (K12).

[0101] The difference between Example B2-B3 and Example B1 lies in the mass percentage of waste quartz powder and the mass percentage of water. Other process parameters are the same. The specific parameters and experimental results are shown in Table 2-1 and Table 2-2.

[0102] Table 2-1 Parameters of the second embodiment

[0103]

[0104]

[0105] Table 2-2 Experimental results of the second group of embodiments

[0106]

[0107] The results of the second group of examples show that as the mass percentage of the first ceramic powder decreases, the through porosity increases, the separation efficiency decreases, and the oil contact angle fluctuates but is generally at a high level. When the mesh size of the first ceramic powder is the same, the thickness of the interception layer is not much different.

[0108] The third group of embodiments includes embodiments C1-C5. In embodiment C1, the main materials are as follows: 40% of the first ceramic powder, 12% of the single crystal silicon powder, and 48% of water, and the auxiliary materials include 1% of the total mass of the main materials as an adhesive, 1% of a dispersant, and 0.7% of a foaming agent. The first ceramic powder is a diatomaceous earth powder with a silicon dioxide content of 82% and a mesh size of 325, the single crystal silicon powder has a silicon content of 95% and a mesh size of 325, the adhesive is xanthocollagen, the dispersant is a polyvinyl alcohol copolymer, and the foaming agent is sodium dodecyl sulfate (K12).

[0109] The difference between whisker reinforced double-layer porous ceramic plate embodiments C2-C5 and embodiment C1 lies in the mass percentage of the first ceramic powder, the mass percentage of single crystal silicon and the mass percentage of water. Other process parameters are the same. The specific parameters and experimental results are shown in Table 3-1 and Table 3-2.

[0110] Table 3-1 Parameters of the third group of embodiments

[0111]

[0112]

[0113] Table 3-2 Experimental results of the third group of embodiments

[0114]

[0115] The results of the third group of examples show that as the mass percentage of the first ceramic powder decreases, the through porosity increases and the separation efficiency decreases. As the mass percentage of the single crystal silicon powder decreases, the through porosity increases and the separation efficiency decreases. When the mass percentage of the single crystal silicon powder is 9%, the separation efficiency drops below 90%. When the mesh size of the first ceramic powder is the same, the thickness of the interception layer is not much different.

[0116] Figure 7 A whisker-reinforced double-layer porous ceramic plate sample prepared using Example B2 is shown, which has a diameter of 240 mm, a thickness of 12 mm, and an effective membrane area of ​​0.045 square meters.

[0117] Figure 8 Shows the oil and Figure 7Schematic diagram of the contact angle of the medium whisker reinforced double-layer porous ceramic plate sample, with a contact angle of 132°.

[0118] Fig. 9 Shows Figure 7 Comparison of the sample of the medium whisker reinforced double-layer porous ceramic plate before and after filtering oily wastewater. The left side of the figure shows the wastewater before filtration, the right side shows the wastewater after filtration, and the middle side shows the oil separated from the wastewater. It can be seen intuitively from the figure that before filtration, the wastewater is turbid and yellowish brown due to the presence of more solid particles and oil. After filtration, the wastewater becomes clear. In this embodiment, before filtration, the TOC of the wastewater is 15763 mg / L, and after filtration, the TOC of the wastewater is 267.58 mg / L, and the separation efficiency is 98.3%.

[0119] Fig.10 The flux diagram of the treatment of oily wastewater generated by a cold-rolled galvanizing line of a steel plant using the whisker-reinforced double-layer porous ceramic plate prepared in Example A1 is shown. In this embodiment, the oil content and solid particle content in the oily wastewater change over time, and backwashing is performed when the filtration flux drops to about 60% of the initial filtration flux. The backwashing time is 5 seconds, and the filtration flux measurement is performed every 10 minutes. It can be seen from the figure that when filtering using the whisker-reinforced double-layer porous ceramic plate, the filtration flux will decrease over time, but after backwashing, the filtration flux is restored.

[0120] The present disclosure also provides a method for preparing a whisker-reinforced porous ceramic plate, comprising the following steps:

[0121] S21, mixing the main materials including the first ceramic powder, the single crystal silicon powder and water with the adhesive and the dispersant to form a first mixed slurry, wherein the silicon dioxide content of the first ceramic powder is ≥70%;

[0122] S22, adding a foaming agent to the first mixed slurry and stirring to form a foam slurry;

[0123] S23, injecting the foam slurry into the mold, and taking out the ceramic blank after natural drying;

[0124] S24, using a carbon embedding sintering method to embed the ceramic blank into carbon for sintering, heating the temperature to 1000-1200° C. at a heating rate of 4-10° C. / min, and keeping the temperature for more than 1 hour to obtain a whisker-reinforced porous ceramic plate.

[0125] The difference between the whisker-reinforced porous ceramic plate prepared by the above method and the whisker-reinforced double-layer porous ceramic plate preparation method disclosed in the present invention is that when preparing the ceramic blank, it is not necessary to cover the mold with oil paper, and no interception layer is formed, so there is no need to use the second ceramic powder dry powder to fill the pores of the interception layer of the ceramic rough blank. The main materials, auxiliary materials, mass percentage, mesh number and other technical features are the same as those in the above-mentioned whisker-reinforced double-layer porous ceramic plate preparation method.

[0126] Since the above preparation method does not cover the mold with oil paper, no interception layer is formed. Its structure is the same as the support layer of the whisker-reinforced double-layer porous ceramic plate, with a cavity structure containing whiskers with a mesh structure, and a through porosity greater than 50%, for example, 50%-80%.

[0127] In order to further improve the hydrophilicity and oleophobicity, after the heat preservation step of step S24, step S25 is further included:

[0128] S25, soaking the whisker-reinforced ceramic blank obtained by calcination in an amphoteric fluorocarbon surfactant solution, taking it out and drying it, so as to obtain a whisker-reinforced porous ceramic plate.

[0129] Through step S25, the outer surface layer and the inner pore surface layer of the whisker-reinforced double-layer porous ceramic plate obtained have a hydrophilic film layer, which further improves its hydrophilicity and oleophobicity.

[0130] The fourth group of embodiments includes embodiments D1 and D2. Each embodiment uses steps S21-S25, but the difference is that the first ceramic powder is different. The specific steps of each embodiment are as follows: S21, the main material including the first ceramic powder, the single crystal silicon powder and the water is stirred and mixed with the adhesive and the dispersant, the stirring rate is 3000 rpm, the stirring time is 45 minutes, and the first mixed slurry is formed; S22, the foaming agent is added to the first mixed slurry and stirred and mixed, the stirring rate is 3000 rpm, the stirring time is 10 minutes, and the foam slurry is formed; S23, the foam slurry is injected into a circular mold, naturally dried for 60 hours, heated to 50 ℃-100 ℃ and continued to dry for 3 hours, and then the ceramic blank is taken out; S24, the ceramic blank is buried in carbon twice the thickness of the ceramic blank by using the carbon sintering method, and the temperature is raised to 1200 ℃ at a heating rate of 4-10 ℃ / min, and the temperature is kept for 3 hours to obtain a whisker-reinforced ceramic blank; S25, the whisker-reinforced ceramic blank is placed in 5% The whisker-reinforced porous ceramic plate was obtained by immersing the plate in a FS-50 aqueous solution for 1 hour and then taking it out and drying it.

[0131] Example D1 is based on Example C4, but the inventor omits the steps of covering the mold surface with oil paper and filling the pores of the intercepting layer of the ceramic rough blank with the second ceramic powder, and replaces the adhesive.

[0132] In Example D1, the main materials are as follows: 38% of the first ceramic powder, 12% of the single crystal silicon powder, and 50% of water, and the auxiliary materials include 1% of the total mass of the main materials as an adhesive, 1% of the dispersant, and 0.7% of the foaming agent. The first ceramic powder is a diatomaceous earth powder with a silicon dioxide content of 82% and a mesh size of 325 meshes, the single crystal silicon powder has a silicon content of 95% and a mesh size of 325 meshes, the adhesive is sodium cellulose, the dispersant is a polyvinyl alcohol copolymer, and the foaming agent is sodium dodecyl sulfate (K12).

[0133] The only difference between Example D2 and Example D1 is that the first ceramic powder is replaced by quartz with a silicon dioxide content of 95% and a mesh size of 325 from diatomaceous earth.

[0134] The specific parameters are shown in Table 4.

[0135] Table 4 Parameters of the fourth embodiment

[0136]

[0137] Fig.11 A comparison chart of the whisker-reinforced porous ceramic plate sample prepared in Example D1 before and after filtering oily wastewater is shown. The left side of the figure shows the wastewater before filtration, and the right side shows the wastewater after filtration. It can be seen intuitively from the figure that before filtration, the wastewater is relatively turbid and yellow due to the presence of more solid particles and oil. After filtration, the color of the wastewater becomes lighter and the transparency increases. In this embodiment, before filtration, the TOC of the wastewater is 1157.43 mg / L, and after filtration, the TOC of the wastewater is 268.096 mg / L, and the separation efficiency is 76.80%.

[0138] The inventors of the present disclosure further discovered through experiments that although the whisker reinforced porous ceramic plates prepared using different ceramic powders have similarities in material structure, due to the differences in the properties of different materials, there are differences in the service life of the whisker reinforced porous ceramic plates prepared using ceramic powders of different materials. Fig.12 The pure water flux test of the whisker reinforced porous ceramic plates prepared in Example D1 and Example D2 is shown, and the pure water flux obtained under the same test conditions changes with time. It can be seen from the figure that the pure water flux of the whisker reinforced porous ceramic plate prepared from diatomaceous earth drops rapidly after being used for more than 4 hours; while the pure water flux of the whisker reinforced porous ceramic plate prepared from quartz remains stable even after being used for more than 48 hours. Observation of the used whisker reinforced porous ceramic plates found that after being soaked in water for a long time, the whisker reinforced porous ceramic plates prepared from diatomaceous earth expanded, causing the through holes to be blocked, thereby causing a decrease in water flux, while the whisker reinforced porous ceramic plates prepared from quartz did not expand, so that a stable flux could be maintained for a long time.

[0139] Since the main difference between the whisker reinforced double-layer porous ceramic plate and the whisker reinforced double-layer porous ceramic plate is that the former has an interception layer, it is understandable that the whisker reinforced double-layer porous ceramic plate made of diatomaceous earth will also expand after a period of use, while the whisker reinforced double-layer porous ceramic plate made of quartz will not expand even after a long period of use and has stable physical properties.

[0140] The method for preparing a whisker-reinforced double-layer porous ceramic plate disclosed in the present invention uses a first ceramic powder with a silicon dioxide content of ≥70%, a single crystal silicon powder and water as the main materials, and uses oil paper on the surface of a mold to make a blank on the basis of a foamed ceramic process, thereby forming an extremely thin surface layer with pores, i.e., an interception layer, and a support layer with a cavity structure having a large number of voids on the surface of the prepared ceramic blank, and then burying the prepared ceramic blank in carbon and reacting with it, so that whiskers with a mesh structure are generated in the cavity structure. When the whisker-reinforced double-layer porous ceramic plate prepared by this method is used to filter sewage containing solid particles and oil, the separation efficiency is high, the filtering effect on solid particles is good, and it is not easy to be blocked.

[0141] On the basis of the prepared ceramic rough blank, dry powder is further used to fill the pores of the interception layer of the ceramic rough blank, so that without increasing the thickness of the interception layer, the number of pores in the interception layer of the ceramic rough blank with a pore size larger than the preset filter pore size is greatly reduced, the number of large-sized solid particles passing through the interception layer is reduced, and the filtration effect is improved.

[0142] Furthermore, by soaking in an amphoteric fluorocarbon surfactant solution, a hydrophilic film layer is formed on the outer surface and the inner pore surface of the whisker-reinforced ceramic blank, further enhancing its hydrophilicity and oleophobicity, improving separation efficiency, reducing the adhesion of oil droplets on the surface, and reducing the clogging rate.

[0143] In addition, since the whisker-reinforced double-layer porous ceramic plate disclosed in the present invention has an extremely thin interception layer, and the aperture of the through-holes of the interception layer is small, and the supporting layer has the characteristics of a large-sized cavity structure, the solid particles blocking the through-holes of the interception layer and the oil accumulated in the cavity of the supporting layer can be removed by backwashing the whisker-reinforced double-layer porous ceramic plate after use for a period of time, and the filtration flux can be restored. Therefore, the whisker-reinforced double-layer porous ceramic plate disclosed in the present invention can be used repeatedly, reducing the cost of cleaning and replacement.

[0144] In addition, the present disclosure further selects quartz ceramic powder as the basic material to obtain a whisker-reinforced double-layer porous ceramic plate with stable physical properties and long-term use, making the present invention suitable for large-scale industrial applications.

[0145] A person skilled in the art can understand and implement other changes to the disclosed embodiments by reading the specification, the disclosed content, the drawings and the attached claims, and they all fall within the scope of protection of the claims of the present disclosure without departing from the essence of the claims of the present disclosure.

Claims

1. A whisker reinforced double-layer porous ceramic plate, characterized in that: The whisker-reinforced double-layer porous ceramic plate includes an intercepting layer and a supporting layer, the intercepting layer has through holes, the proportion of through holes with a pore size greater than 50 μm in the intercepting layer is less than 20% of the number of through holes with a pore size greater than 5 μm, the thickness of the intercepting layer is 45-120 μm, the supporting layer has a cavity structure, the pore size of the cavity structure of the supporting layer is greater than the pore size of the through holes of the intercepting layer, the through holes of the intercepting layer are connected to the cavity structure, the cavity structure has whiskers with a mesh structure, the diameter of the whiskers is 50-150 nm, and the through porosity of the whisker-reinforced double-layer porous ceramic plate is greater than 50%.

2. The whisker reinforced double-layer porous ceramic plate according to claim 1, characterized in that: The through porosity of the whisker-reinforced double-layer porous ceramic plate is 54%-80%.

3. The whisker reinforced double-layer porous ceramic plate according to claim 1, characterized in that: The arresting layer is formed by using oil paper on the mold surface.

4. The whisker reinforced double-layer porous ceramic plate according to claim 1, characterized in that: The whiskers are silicon dioxide whiskers.

5. The whisker reinforced double-layer porous ceramic plate according to claim 1, characterized in that: The thickness of the support layer is 8-32 mm.

6. The whisker reinforced double-layer porous ceramic plate according to claim 1, characterized in that: The outer surface layer and the inner pore surface layer of the whisker-reinforced double-layer porous ceramic plate are provided with a hydrophilic film layer.

7. The whisker reinforced double-layer porous ceramic plate according to claim 6, characterized in that: The hydrophilic membrane layer is an amphoteric fluorocarbon surfactant.

8. The whisker reinforced double-layer porous ceramic plate according to claim 1, characterized in that: The cavity structure of the support layer is formed by a foaming process.

9. The whisker reinforced double-layer porous ceramic plate according to claim 1, characterized in that: The whisker-reinforced double-layer porous ceramic plate is prepared by using quartz powder.

10. A method for preparing a whisker-reinforced double-layer porous ceramic plate, characterized in that: The method comprises the following steps: S1. A main material including a first ceramic powder, a single crystal silicon powder and water is stirred and mixed with an adhesive and a dispersant to form a first mixed slurry, wherein the silicon dioxide content of the first ceramic powder is ≥70%, and the silicon content of the single crystal silicon powder is ≥95%; S2, adding a foaming agent to the first mixed slurry and stirring to form a foam slurry; S3, injecting the foam slurry into at least one mold covered with oil paper, and taking out the ceramic rough embryo after natural drying, wherein the contact surface between the ceramic rough embryo and the oil paper forms an interception layer; S4, filling the pores of the intercepting layer of the ceramic rough blank with a second ceramic powder dry powder to form a ceramic blank; S5, using a carbon embedding sintering method to embed the ceramic blank into carbon for sintering, heating the temperature to 1000-1200° C. at a heating rate of 4-10° C. / min, and keeping the temperature for more than 1 hour to obtain the whisker-reinforced double-layer porous ceramic plate, The main materials are as follows according to mass percentage: the first ceramic powder is 23-60%, the single crystal silicon powder is 10-15%, the water is 25-67%, and the adhesive, the dispersant and the foaming agent are all 0.3-2% of the total mass of the main materials.

11. The preparation method according to claim 10, characterized in that: After the heat preservation step in step S5, the method further comprises the following steps: S6, soaking the ceramic blank obtained by calcination in an amphoteric fluorocarbon surfactant solution, taking it out and drying it to obtain the whisker-reinforced double-layer porous ceramic plate, Wherein, the concentration of the amphoteric fluorocarbon surfactant solution is 5% to 8%.

12. The preparation method according to claim 10, characterized in that: The main materials are as follows in terms of mass percentage: the first ceramic powder is 38-50%, the single crystal silicon powder is 10-12%, and the water is 38-52%; the adhesive, the dispersant and the foaming agent are 1-2%, 1-2%, and 0.3-1% of the total mass of the main materials, respectively.

13. The preparation method according to claim 10, characterized in that: The mesh size of the first ceramic powder is 200-500 meshes.

14. The preparation method according to claim 10, characterized in that: The mesh size of the single crystal silicon powder is 200-500 meshes.

15. The preparation method according to claim 10, characterized in that: The first ceramic powder is any one or more of quartz, diatomaceous earth, and silica, and the second ceramic powder is any one or more of quartz, diatomaceous earth, silica, mullite, kaolin, sepiolite, and dolomite.

16. The preparation method according to claim 15, characterized in that: The first ceramic powder and the second ceramic powder are both quartz.

17. The preparation method according to claim 10, characterized in that: The adhesive is any one or more of sodium carboxymethyl cellulose, hydroxyethyl cellulose, xanthan gum and gelatin.

18. The preparation method according to claim 10, characterized in that: The foaming agent is any one or more of sodium dodecyl sulfate, sodium dodecylaminopropionate, triethanolamine lauryl sulfate, and carbonates.

19. The preparation method according to claim 10, characterized in that: The dispersant is any one or more of polyvinyl alcohol, polyvinyl alcohol copolymer, modified starch, silicone resin polyether emulsion.

20. A whisker-reinforced double-layer porous ceramic plate prepared by the preparation method according to any one of claims 10 to 19.

21. Use of the whisker reinforced double-layer porous ceramic plate according to any one of claims 1 to 9 or 20 in separation of oil and water containing solid particles.

Citation Information

Patent Citations

  • Porous ceramic membrane material as well as preparation method and application thereof

    CN110981529A